The Influence Of Immersive Learning Approach And Digital Interactive Board Media On Student Learning Motivation In Elementary Schools - Mariyanti Mascarinhas; Juliana M Sumilat; Richard D. H. Pangkey (Lembaga Bale Literasi, 2026)
This study aims to examine the effect of the deep learning approach and interactive digital board media on elementary school students’ learning motivation. The research employed a quantitative approach with a quasi-experimental method using a posttest-only control group design. The sample consisted of 40 fifth-grade students divided into an experimental group and a control group. Data were collected using a Likert-scale questionnaire consisting of 30 items measuring six indicators of learning motivation. The results showed that the experimental group had a higher mean score (136.50) compared to the control group (127.20). The independent sample t-test revealed a significant difference (t = 4.249; p < 0.001), indicating that the integration of deep learning and interactive digital boards significantly improves students’ motivation. The effect size analysis using Cohen’s d resulted in a value of 1.34, categorized as a large effect. These findings suggest that combining deep learning approaches with interactive digital media creates a more engaging and meaningful learning environment, significantly enhancing students' motivation. Therefore, integrating digital technology with student-centered pedagogy is highly recommended in elementary education.